2018
DOI: 10.1038/s41598-018-26821-7
|View full text |Cite
|
Sign up to set email alerts
|

Diametric effects of autism tendencies and psychosis proneness on attention control irrespective of task demands

Abstract: Our capacity to attend a target while ignoring irrelevant distraction impacts our ability to successfully interact with our environment. Previous reports have sometimes identified excessive distractor interference in both autism and schizophrenia spectrum disorders and in neurotypical individuals with high subclinical expressions of these conditions. Independent of task, we show that the direction of the effect of autism or psychosis traits on the suppression or rejection of a non-target item is diametrical. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…This suggests that the PAUSS and PANSS positive symptoms are associated with diametric influences on sustained attention independent of the disorder. This is consistent with (i) the diametric model (52, 53)-which posits that ASD and SSD are characterized by opposing phenotypic patterns-, (ii) evidence suggesting that ASD and SSD can be characterized by opposing patterns of attentional abilities (3,54), and (iii) existing evidence suggesting that the presence of both disorders may be associated with attenuated impairments (3,27,38). Importantly, this pattern of association also suggests that the omission errors in ASD and SPD might be precipitated by different mechanisms, which is consistent with the notion that apparent overlaps between autism and schizophrenia spectrum disorders might be precipitated by different cognitive styles or biases (55,56).…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that the PAUSS and PANSS positive symptoms are associated with diametric influences on sustained attention independent of the disorder. This is consistent with (i) the diametric model (52, 53)-which posits that ASD and SSD are characterized by opposing phenotypic patterns-, (ii) evidence suggesting that ASD and SSD can be characterized by opposing patterns of attentional abilities (3,54), and (iii) existing evidence suggesting that the presence of both disorders may be associated with attenuated impairments (3,27,38). Importantly, this pattern of association also suggests that the omission errors in ASD and SPD might be precipitated by different mechanisms, which is consistent with the notion that apparent overlaps between autism and schizophrenia spectrum disorders might be precipitated by different cognitive styles or biases (55,56).…”
Section: Discussionsupporting
confidence: 86%
“…However, it is important to also note, as is also evident from Figures 3c and 4c, that a shift from reactive to proactive control strategy greatly diminishes the ability of individuals with high positive schizotypal traits to flexibly generate unique ideas across contexts. This is consistent with research in patients with schizophrenia (Boudewyn, Scangos, Ranganath, & Carter, 2020;Lesh et al, 2013) and neurotypicals with high positive schizotypal traits (Abu-Akel et al, 2018) who exhibited a decline in performance in tasks requiring proactive compared to reactive control. The notion of latent inhibition-the inability to filter out previously experienced events or contexts as irrelevant-which is considered an endophenotype of schizotypy (Lubow & Gewirtz, 1995) and specifically positive schizotypy , might help explain the uneven performance of these individuals across contexts when deploying a proactive control strategy.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to cognitive control, research suggests that individuals with elevated positive schizotypal traits or at-risk state for psychosis are associated with deficits in applying proactive control and appear to have no major deficit in, and even a bias toward reactive control (Abu-Akel et al, 2018;Niendam et al, 2014). In the context of creative thinking research, it has been shown that the association of positive schizotypy with increased ability of unusual associations-defined as statistically infrequent or "unique" associations-was not related to proactive interferences, that is, when irrelevant and older information had to be deleted from memory (Rominger, Weiss, Fink, Schulter, & Papousek, 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional converging evidence comes from studies of young adults with high expression of psychosis proneness, who have been shown to favor reactive distractor suppression relative to proactive distractor suppression (Abu-Akel et al, 2016a;2016b;2016c). In the t-task described above, performance benefits from the presence of the salient distractor scale with the expression of psychosis proneness (Abu-Akel et al, 2018), highlighting that this paradigm is sensitive enough to detect variations in the magnitude of engagement of reactive distractor suppression.…”
Section: Introductionmentioning
confidence: 99%